Brainstorming in industrial design education: is there mediation effect? / Amer Shakir Zainol ... [ et al.] - Zainol, Amer Shakir; Azahari, Mustaffa Halabi; Mastor, Khairul Anwar; Mohd Sanusi, Zuraidah; Mohd Yusof, Wan Zaiyana (Universiti Teknologi MARA, Perlis, 2011)
Since Osborn (1957) introduced the technique that was very valuable to create new ideas, the technique has been applied tremendously in various area and disciplines. Without exception, in industrial design practices, group brainstorming is also a tool that is much preferred by designers to elicit creative ideas. Undergraduates also are exposed with this technique to generate the creative ideas. This is because, they are always dealing with the problem of human everyday; make a better design for the sake of human. This technique emphasizes in the group. There are many factors have been determined by prior research. The prominent production loss that is disturbing this technique is Production Blocking. This study examines two main factors, personality traits and Ownership of the topic which influence Production Blocking in group brainstorming. Personality can be referred to as a consistent behavior pattern and intrapersonal processes within the individual. Ownership of the topic relates to the interest of individuals in engaging the brainstorming activities especially in industrial design. Production Blocking includes competition to speak among individuals. 115 groups which consist of 460 Industrial Design undergraduates across 6 public universities have participated in this study. The hypotheses are tested using analysis of Partial Least Squares (PLS) regression. Results show that personality of Extraversion and Openness are negatively significant related to the Production Blocking. However, Emotional Stability is not significantly related to Production Blocking. Results also reveal that Extraversion, Emotional Stability, and Openness are positively significant related to Ownership of the Topic. In accordance with the expectations, Ownership of the topic is positively significant related to Production Blocking. Results also demonstrate that Ownership of the Topic mediates the relationships between personality traits of Extraversion, Emotional Stability, and Openness and Production Blocking. In other words, groups that are high on these three personality traits would owned the topic given subsequently, reduce competition of speaking time during brainstorming session. The results are of potential interest to industrial design context, educators, and researchers.